2011
DOI: 10.5588/ijtld.10.0788
|View full text |Cite
|
Sign up to set email alerts
|

Completion of isoniazid preventive therapy and survival in HIV-infected, TST-positive adults in Tanzania

Abstract: Completion of IPT is associated with increased survival in HIV-infected adults with CD4 counts ≥ 200 cells/μ l and a positive TST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
1
26
1
2
Order By: Relevance
“…Similar assessments were done in Brazil and South Africa and comparable results were documented in the effectiveness of IPT with ART while IPT coverage (10 and 13% respectively) and effectiveness of ‘IPT only’ (43 and 13% respectively) were much lower than the findings from our study [5], [6]. In a different study in Tanzania, IPT was not found to be effective at all [20]. Our study presents new evidence on the effect of timing of IPT initiation with respect to ART.…”
Section: Discussionsupporting
confidence: 86%
“…Similar assessments were done in Brazil and South Africa and comparable results were documented in the effectiveness of IPT with ART while IPT coverage (10 and 13% respectively) and effectiveness of ‘IPT only’ (43 and 13% respectively) were much lower than the findings from our study [5], [6]. In a different study in Tanzania, IPT was not found to be effective at all [20]. Our study presents new evidence on the effect of timing of IPT initiation with respect to ART.…”
Section: Discussionsupporting
confidence: 86%
“…Although not universally detected, several studies have shown improved survival among IPT recipients: completion of 6IPTwas associated with a 60% reduction in mortality in a Tanzanian cohort of TST-positive HIV-infected participants with baseline CD4 + cell count at least 200 cells/μl and with access to ART [20]; a retrospective analysis of South African miners initiating ART showed that 6IPT reduced their risk of death by 66% [21]. The Soweto IPT trial observed the lowest rate of ‘death or TB’ in TST-positive HIV-infected participants receiving 36IPT [15].…”
Section: Discussionmentioning
confidence: 99%
“…This initiative requires further implementation research. del 95% 0,03-0,28) y el hecho de recibir una reserva de isoniazida para 2 meses al comienzo del ciclo, y el factor que se asoció con un mayor riesgo de no finalizar el tratamiento fue cuando el paciente había incumplido citas médicas antes de comenzar el tratamiento (ORa 5,25; IC95% 2,(10)(11)(12)(13)14). Conclusión: Las tasas de finalización del TPI en los siete centros pilotos de Zimbabue fueron relativamente altas e indican que es factible desplegar esta iniciativa en los establecimientos públicos de salud.…”
Section: Public Health Action Ipt In Zimbabwe 59unclassified